Development of a knowledge-based expert system for intersection improvement - De Guzman, Mark P. (College of Engineering, University of the Philippines Diliman, 2010)
Intersections are vulnerable to traffic congestion and road crashes when poorly designed. Moreover, an intersection must be periodically checked if the design is still suitable to current conditions as volume of vehicles increases with time. Guidelines for improving intersection developed by the National Cooperative Highway Research Program (NCHRP) Report No. 457 is a step by step procedure which provides technical guides in selecting potential alternatives in a specific intersection problem. This reference is available but do not interactively relate to the traffic engineer. To reduce this complexity, the study developed a Knowledge-Based Expert System (KBES).